Proceso atención de enfermería en paciente de 62 años de edad con tuberculosis renal. - Naranjo Bazantes, Jessica Guadalupe (2023)
Renal tuberculosis is a form of extrapulmonary tuberculosis that affects the urinary tract and kidneys. It is caused by the bacterium Mycobacterium tuberculosis and can affect people of any age, but it is more common in adults. The infection is usually caused by inhalation of the bacteria, but it can also occur by spread of the infection from other organs. Symptoms of renal tuberculosis can include pain in the lower back, frequent and painful urination, blood in the urine, fever, and night sweats. The diagnosis of renal tuberculosis is made by laboratory tests and imaging tests. Treatment of renal tuberculosis consists of the administration of a combination of antibiotics for several months in severe cases, surgical removal of the infected kidney may be necessary. It is important to treat renal tuberculosis appropriately to prevent complications such as permanent kidney damage and sepsis. Through the development of this clinical case, I was able to observe the patterns that are altered according to the model of Marjory Gordon, in a patient with renal tuberculosis, from the Los Trigales Health Center in the city of Guaranda, Province of Bolívar, in which the nursing care process to provide nursing care, through the application of the NANDA,NIC,NOC tetralogy.